Reducing hospital readmissions amongst people experiencing homelessness: a mixed-methods evaluation of a multi-disciplinary hospital in-reach programme - Stephen Malden; Lawrence Doi; Lauren Ng; Fiona Cuthill (BMC, 2023)
Abstract Introduction People experiencing homelessness are at increased risk of experiencing ill-health. They are often readmitted to hospital after discharge, usually for the same or similar reasons for initial hospitalisation. One way of addressing this issue is through hospital in-reach initiatives, which have been established to enhance the treatment and discharge pathways that patients identified as homeless receive after hospital admission. Since 2020, the Hospital In-reach programme (which involves targeted clinical interventions and structured discharge support) has been piloted in two large National Health Service (NHS) hospitals in Edinburgh, United Kingdom (UK). This study describes an evaluation of the programme. Methods This evaluation used a mixed method, pre-post design. To assess the effect of the programme on hospital readmission rates from baseline (12 months pre-intervention) and follow-up (12 months post-intervention), aggregate data describing the proportions of homeless-affected individuals admitted to hospital during the evaluation period were analysed using Wilcoxon signed rank test, with level of significance set at p = 0.05. Qualitative interviews were conducted with fifteen programme and hospital staff (nurses, general practitioners, homeless link workers) to assess the processes of the programme. Results A total of 768 referrals, including readmissions, were made to the In-reach programme during the study period, of which eighty-eight individuals were followed up as part of the study. In comparison to admissions in the previous 12 months, readmissions were significantly reduced at 12 months follow-up by 68.7% (P = 0.001) for those who received an in-reach intervention of any kind. Qualitative findings showed that the programme was valued by hospital staff and homeless community workers. Housing services and clinical staff attributed improvements in services to their ability to collaborate more effectively in secondary care settings. This ensured treatment regimens were completed and housing was retained during hospital admission, which facilitated earlier discharge planning. Conclusions A multidisciplinary approach to reducing readmissions in people experiencing homelessness was effective at reducing readmissions over a 12-month period. The programme appears to have enhanced the ability for multiple agencies to work more closely and ensure the appropriate care is provided for those at risk of readmission to hospital among people affected by homelessness.